Diabetic retinopathy: loss of neuroretinal adaptation to the diabetic metabolic environment. (27th March 2014) - Abcouwer, Steven F.; Gardner, Thomas W.
Abstract : Diabetic retinopathy (DR) impairs vision of patients with type 1 and type 2 diabetes, associated with vascular dysfunction and occlusion, retinal edema, hemorrhage, and inappropriate growth of new blood vessels. The recent success of biologic treatments targeting vascular endothelial growth factor (VEGF) demonstrates that treating the vascular aspects in the later stages of the disease can preserve vision in many patients. It would also be highly desirable to prevent the onset of the disease or arrest its progression at a stage preceding the appearance of overt microvascular pathologies. The progression of DR is not necessarily linear but may follow a series of steps that evolve over the course of multiple years. Abundant data suggest that diabetes affects the entire neurovascular unit of the retina, with an early loss of neurovascular coupling, gradual neurodegeneration, gliosis, and neuroinflammation occurring before observable vascular pathologies. In this article, we consider the pathology of DR from the point of view that diabetes causes measurable dysfunctions in the complex integral network of cell types that produce and maintain human vision.